An analysis of Islamic environmental ethics with special reference to Malaysia - Kadikon, Sulaiman (2004)
The general term 'environment' has a very wide connotations and concern for this issue has increased, particularly in the last three decades. The environmental crisis has become a widespread matter, the implications of which are global rather than merely international, national or local. Consequently, mankind is attempting to find solutions to this extensive problem and discussion of environmental ethics is expressed through a variety of backgrounds, such as, religious, political and economic ideologies etc. Therefore, as the concern of environmental ethics has become one of the important contemporary topics, it is important for Muslims to contribute such ethical debates. What does Islam offer to solve environmental problems, particularly in Islamic states? To realise this objective, Malaysia has been cited in this research as one of the Islamic states, which is developing and thus dependent on its natural resources. Malaysia is facing a real challenge to strike the balance between the environment and development, particularly in the case study of the Bakun Hydro Electrical Project, Sarawak, Malaysia.